Integrated evolutionary analysis reveals antimicrobial peptides with limited resistance - Réka Spohn (Nature Portfolio, 2019)
Antimicrobial peptides (AMPs) are emerging as drug candidates, but the risk of pathogen resistance is not well understood. Here, the authors investigate AMP resistance evolution in E. coli, finding physicochemical features that make AMPs less prone to resistance and no cross- or horizontally-acquired resistance.